2022
DOI: 10.1091/mbc.e22-05-0188
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis underlying the ciliary defects caused by IFT52 variations found in skeletal ciliopathies

Abstract: Mutations of IFT52, a subunit of the IFT-B complex, cause skeletal ciliopathies. IFT52 variants found in ciliopathy individuals are compromised in terms of IFT-B complex formation from two subcomplexes and its interaction with kinesin-II. IFT52-KO cells expressing IFT52 variants showed mild ciliogenesis defects and a decrease in ciliary IFT-B level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(228 reference statements)
0
6
0
Order By: Relevance
“…21 It is reported that the hetero-tetramer complex of IFT38, IFT52, IFT57 and IFT88 recruits the kinesin-II proteins (KIF3A/KIF3B/KAP3) to the IFT complex. 21,81 Of the four IFT proteins, IFT52 has the most important function in mediating the interaction with KIF3B of the kinesin-II complex. 21 However, many of the other IFT proteins perform additional functions to enhance the interaction of IFT-B with kinesin-II.…”
Section: Coordination Of Ift Complexes and Regulation Of Ciliary Tran...mentioning
confidence: 99%
See 3 more Smart Citations
“…21 It is reported that the hetero-tetramer complex of IFT38, IFT52, IFT57 and IFT88 recruits the kinesin-II proteins (KIF3A/KIF3B/KAP3) to the IFT complex. 21,81 Of the four IFT proteins, IFT52 has the most important function in mediating the interaction with KIF3B of the kinesin-II complex. 21 However, many of the other IFT proteins perform additional functions to enhance the interaction of IFT-B with kinesin-II.…”
Section: Coordination Of Ift Complexes and Regulation Of Ciliary Tran...mentioning
confidence: 99%
“…The IFT complex consists of two multi-subunit subcomplexes, IFT-A and IFT-B. The formation of the IFT complex at the ciliary base is initiated by the spontaneous assembly of 16 different proteins (IFT20, 22,25,27,38,46,52,54,56,57,70,74,80,81,88 and 172) which form the complex structure of IFT-B. 17,18 Topologically, the IFT-B complex is divided into two subregions, referred to as the core (IFT-B1) and periphery (IFT-B2).…”
Section: Structural Features Of Ift52 In Context Of Ift-b Complexmentioning
confidence: 99%
See 2 more Smart Citations
“… 14 Ift is driven by two molecular motors, involving cytoplasmic dynein2, which mediates transport from tip to base, and the heterotrimeric kinesin-2 complex comprised of Kif3a, Kif3b, and Kap3, which is responsible for transport from base to tip. 15 , 104 , 105 Mutations in the gene encoding the heavy chain of cytoplasmic dynein2 cause axoneme swelling because Ift-related proteins are trapped in cilia due to disruption of retrograde transport. 14 Gli cooperates with Kif3a and Kap3, where the interaction of Kap3 restricts Gli transcriptional activity.…”
Section: Hedgehog Signaling and The Primary Ciliummentioning
confidence: 99%